Accessibility controls selective degradation ofphotosystem II subunits by FtsH protease - Krynická,V; Shao,S; Nixon,PJ; Komenda,J (Nature Plants, 2015)
The oxygen-evolving photosystem II (PSII) complex located inchloroplasts and cyanobacteria is sensitive to light-induceddamage1 that unless repaired causes reduction in photosyntheticcapacity and growth. Although a potential target forcrop improvement, the mechanism of PSII repair remainsunclear. The D1 reaction center protein is the main target forphotodamage2, with repair involving the selective degradationof the damaged protein by FtsH protease3. How a singledamaged PSII subunit is recognized for replacement isunknown. Here, we have tested the dark stability of PSII subunitsin strains of the cyanobacterium Synechocystis PCC6803 blocked at specific stages of assembly. We have foundthat when D1, which is normally shielded by the CP43subunit, becomes exposed in a photochemically active PSIIcomplex lacking CP43, it is selectively degraded by FtsH evenin the dark. Removal of the CP47 subunit, which increasesaccessibility of FtsH to the D2 subunit, induced dark degradationof D2 at a faster rate than that of D1. In contrast,CP47 and CP43 are resistant to degradation in the dark. Ourresults indicate that protease accessibility induced by PSII disassemblyis an important determinant in the selection of the D1and D2 subunits to be degraded by FtsH.